Investigating EFL students’ engagement in project-based speaking activities: from a multi-dimensional perspective - Zhong, Jianer; Ismail, Lilliati; Lin, Yueqiao (Frontiers in Psychology, 2025)
IntroductionStudent engagement is essential for improving academic performance and achievement. Project-Based Learning (PBL) has emerged as a promising instructional approach to enhance student engagement. However, its effectiveness across various engagement dimensions remains under-explored.MethodsThis study employed a quasi-experimental mixed-methods approach to examine the impact of PBL on student engagement, with a specific focus on its behavioral, emotional, cognitive, and agentic dimensions. It involved 96 first-year students from a Chinese polytechnic, who were assigned to either an experimental group (n = 49) or a control group (n = 47). While the control group received instruction through conventional teaching methods, the experimental group engaged in PBL. Data were collected through a combination of questionnaires and interviews.ResultsFindings indicate that PBL significantly enhances emotional, behavioral, and cognitive engagement. However, the results also reveal that PBL had no significant effect on agentic engagement. Students perceived PBL as a highly effective method for enhancing engagement, as evidenced by increased strong interest and enjoyment, focused concentration and effort, active use of cognitive strategies, and proactive contribution to learning.DiscussionThis study demonstrates the potential of PBL to foster deeper engagement in EFL settings, particularly in behavioral, emotional, and cognitive dimensions. Nonetheless, its limited effect on agentic engagement suggests a need for instructional adjustments that encourage student autonomy and voice. These findings provide practical insights for educators aiming to implement PBL effectively in EFL classrooms.